Language Interfaces in Adult Heritage Language Acquisition: A Study on Encoding of Nominal Reference in Mandarin Chinese as a Heritage Language - Jin, Jing; Ke, Sihui Echo; Lee, John Chi-Kin (Frontiers in Psychology, 2022)
According to the Interface Hypothesis in the field of bilingualism, the interface connecting a linguistic module with a language-external domain (e.g. syntax-discourse) will present prolonged difficulties for adult bilingual learners, as compared with the interface connecting language-internal modules (e.g. syntax-semantics). This study tested whether the Interface Hypothesis is applicable to the acquisition of Mandarin Chinese as a heritage language. An internet-based acceptability judgment task was administered to 58 advanced and intermediate adult Chinese heritage speakers to collect data in accuracy and reaction time to investigate the adult heritage speakers’ mastery of referential nominal expressions regulated at the syntax-semantics and syntax-discourse interfaces respectively in Mandarin Chinese. The target linguistic phenomena involved three nominal expressions (i.e., the bare N(oun), the [Cl(assifier)-N], and the [Num(eral)-Cl-N]) under four interface-regulated referential readings (i.e., type-denoting, quantity-denoting, indefinite individual-denoting, and definite individual-denoting). In terms of accuracy, the results showed that (i) for the N and the [Num-Cl-N], regardless of the interface type, the advanced group acquired the target phenomena to a nativelike level, who significantly outperformed the intermediate group; (ii) for the [Cl-N], the advanced group exhibited nativelike attainment at the syntax-discourse interface but not at the syntax-semantics interface, and performed significantly better than the intermediate group at both interfaces. Regarding reaction time, no significant differences were reported between the advanced group and the native group for the target structures at either the syntax-semantics or the syntax-discourse interface, while the advanced group performed significantly better than the intermediate group, regardless of the interface type and the structure type. The findings suggest that the nature of the language interface, i.e. whether it pertains to language-external domains (i.e. the external interface) or not (i.e. the internal interface), should not be a reliable factor for predicting the (im)possibility of nativelike attainment of bilingual grammar knowledge, contra the predictions of the Interface Hypothesis. The present study provides new empirical evidence to show that language-external interface properties are not necessarily destined for prolonged difficulties in heritage language acquisition, and that it is possible for adult heritage speakers to make developmental progress in both accuracy and processing efficiency at different types of interfaces.